Characteristics of spatio-temporal distribution of frost/snow disasters in North China during 1644–1911. Issue 1 (31st December 2022) - Bi, Shuoben; Sarfo, Isaac; Xu, Xiuhua; Sun, Jiwei; Zhao, Feng; Qu, Ying
Abstract: This paper presents an analysis based on the use of historical data of frost/snow disasters in North China in combination with ArcGIS and other technical applications. Specifically, the frequency and intensity of frost/snow disasters in North China during the study period, 1644–1911 from the perspective of time and space, were analyzed. We applied the moving average, polynomial fitting, and CEEMD methods. The study yielded the following results: Frost/snow disasters occurred 1982 times during this period. Season wise classification revealed that fall recorded the highest frequency. Based on their annual frequency, the study period was divided into four stages. The CEEMD decomposition of annual frequency sequence revealed a cycle of 2.8 years and 5.3 years on the inter-annual time scale, and 119.4 years on the century-scale. Furthermore, an analysis of spatial distribution of the disasters depicted an uneven frequency distribution; however, an absolute degree of spatial consistency was observed between their grade and the frequency distribution. In Hebei and Henan areas, disasters were lower in frequency and were mainly classified under as mild or moderate grades; however, in Shanxi area, disasters were higher in frequency and corresponded mainly to the severe grade.